PENGARUH METILKOBALAMIN PADA SINDROM TEROWONGAN KARPAL DENGAN DAN TANPA DIABETES MELLITUS - Fasihah Irfani Fitri,* Aida Fithrie,* Aldy S Rambe,* Hasan Sjahrir* (NEURONA, 2015)
BACKGROUND CARPAL TUNNEL SYNDROME CTS IS THE MOST COMMON ENTRAPMENT NEUROPATHY AND ITS INCIDENCE IS INCREASED IN PATIENTS WITH DIABETES MELLITUS DM METHYLCOBALAMIN IS THE ACTIVE FORM OF VITAMIN B12 THAT HAS BEEN WIDELY USED IN PERIPHERAL NEUROPATHY